1-아릴옥시메틸-2,4,5-트리플루오로벤젠 유도체의 합성 및 CCL2 발현의 억제 활성 - 김민정(Min Jung Kim); 조아영(Ahyoung Jo); 김관회(Koanhoi Kim); 곽재환(Jae-Hwan Kwak) (Yaghag-hoi-ji, 2021)
CCL2 overexpression is associated with macrophage recruitment during immune response and poor patientprognosis in various cancers, such as prostate, breast, pancreatic, and liver cancer. For developing CCL2 inhibitors, 1-aryloxymethyl-2,4,5-trifluorobenzene analogs were designed and synthesized by concise synthetic route including SN2reaction, reduction, and oxime formation reaction. Furthermore, it was confirmed that they inhibited CCL2 productioninduced by 27-hydroxycholesterol through reverse transcription PCR in the human acute monocytic leukemia cell line(THP-1). Among them, N-((2-(2,4,5-trifluorobenzyloxy)naphthalene-1-yl)methyl)hydroxylamine (4) exhibited the highestCCL2 transcription inhibition activity. KCI Citation Count: 0